Lower urinary tract function improves after laparoscopic sacrocolpopexy for elderly patients with pelvic organ prolapse. Issue 3 (29th April 2020) - Togo, Mio; Kitta, Takeya; Kanno, Yukiko; Ouchi, Mifuka; Tokiwa, Shino; Huang, Tingwen; Moriyama, Shingo; Nomura, Jimmy; Moriya, Kimihiko; Shinohara, Nobuo
Abstract: Objectives: Pelvic organ prolapse (POP) is relatively common in the elderly population. Laparoscopic sacrocolpopexy (LSC) has been reported by several studies to be a less invasive treatment option as compared to open sacrocolpopexy. However, almost all prior reports focused on the complications or surgical obstacles. The present study was designed to examine POP patients of all ages and assess lower urinary tract function before and after LSC. Methods: This retrospective study examined the results of LSC performed in POP patients. Urodynamic studies were performed pre‐ and postoperatively in 50 patients, with the subjects divided into two groups containing those less than and those older than 65 years of age. We performed a pressure flow study. We examined bladder functions by evaluating bladder capacity, detrusor pressure at maximum flow (PdetQmax), maximum flow rate (Qmax), normal desire to void, strong desire to void, voided volume, and postvoid residual volume (PVR). Statistical analysis was performed using Wilcoxon signed rank test. Values of P  < .05 were considered significant. Results: With regard to the pressure‐flow study parameters, there was a significant increase in the normal desire to void and bladder capacity only in the ≥65 age group. After the operation, there was a significant increase in the mean postoperative Qmax and voided volume, while there was a significant decrease in the PdetQmax and PVR as compared to the preoperative values only in the ≥65 age group. Conclusions: Results show that in elderly patients with POP, LSC might be a valid option with regard to potentially regaining urinary tract function.